Pengaruh Employee Engagement Dan Leader Member Exchange Terhadap Organizational Citizenship Behavior Dengan Mediasi Modal Sosial (Studi Pada Pegawai Yayasan XYZ) - Rizkika Fitri; Hasan Abdul Rozak (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Background - The high level of competition in the field of educational services requires tertiary institutions to continue to improve the quality of human resources, in order to survive in the era of globalization. Organizations really need loyal and highly committed employees in order to survive and develop, therefore researchers are interested in studying the variables Employee Engagement, LMX and OCB. Aim - This study aims to analyze the effect of Employee Engagement and Leader Member Exchange (LMX) on Organizational Citizenship Behavior (OCB) by mediating social capital on employees of the XYZ Foundation. Design / Methodology / Approach – Population in this study were 177 employees of the XYZ Foundation, using a purposive proportional sampling technique, only using a sample of 109 employees. Research testing was carried out by testing validity, reliability, multiple regression analysis, t test, R2 test and moderation test using SPSS 22. Findings – The results showed that: (1) Employee Engagement and LMX have a positive effect on Social Capital and OCB (2) Social Capital positive effect on OCB (3) Social capital mediates the effect of Employee Engagement on OCB, and (4) Social capital mediates the effect of LMX on OCB. Conclusion - The empirical test results identify that the positive attitude resulting from Employee Engagement, LMX and social capital that exists in each employee will foster cooperation between fellow employees and superiors with the aim of personal success, other people and the organization. Research Implication - This research is expected to make a positive contribution to further research, and to become a reference for organizations regarding the influence of employee engagement, LMX and mediation of social capital on OCB. Limitation - The object of this research only took the XYZ Foundation with lecturers, teachers and employees as respondents who were still actively working at the XYZ Foundation.